VRIO-Based Digital Communication Strategies to Enhance Brand Image at the Office of Notary & PPAT Putranto Nur Utomo: STRATEGI KOMUNIKASI DIGITAL BERBASIS VRIO DALAM MENINGKATKAN BRAND IMAGE DI KANTOR NOTARIS & PPAT PUTRANTO NUR UTOMO - Faradita Putri Al Rohman; Hudi Santoso (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study explores the role of digital communication strategies in enhancing the brand image of Notary & PPAT Putranto Nur Utomo. In today’s digital era, the credibility of notarial services is not only determined by legal competence but also by how effectively offices manage communication, administration, and client interactions. The research applies a qualitative approach through direct participation, observation, interviews, and document analysis during an internship program. Data were analyzed using Keller’s Customer-Based Brand Equity (CBBE) model and the VRIO framework to evaluate how internal digital systems affect brand perception. The findings reveal that while the office demonstrates strong credibility in legal competence, its digital communication and administrative practices remain suboptimal. Challenges include non-standardized digital archives, inefficient internal communication, and incomplete staff identity formalization. These weaknesses impact professional perception despite positive assessments of legal services. The novelty of this study lies in its emphasis on internal digitalization as the foundation of brand image building, rather than relying solely on external marketing or social media presence. Strengthening standardized digital archives, structured communication systems, and staff professionalism is recommended to create a sustainable competitive advantage. Ultimately, this research contributes to the development of communication strategies for notary offices to achieve a modern, credible, and client-oriented image.